Physical Modeling of Power Unit in Power Plant with Auxiliary Transformer - Heorhiy Lysiak; Olena Pastukh; Bohdan Kharchyshyn (Energy Engineering and Control Systems)
The article shows the option of the first degree transformation scheme in auxiliary power supply systems of the power unit (PU). The power supply to the auxiliary receivers is carried out from the generator through the working and additional working auxiliary transformers (AAT). The method of switching on the latter one provides its operation in the source mode set by the PU current load. Experiments were carried out on a static physical model of the scheme fragment of the auxiliary power supply system with an AAT. It is confirmed that its natural properties, in contrast to the traditional schemes, provide during the normal modes, modes of external short circuits the level of voltage on the busbars, sufficient for the reliable operation of their electrical receivers. The possibility of effective research with the use of appropriate mathematical and digital models has been proved. The high adequacy of the results has been confirmed.